2011
DOI: 10.1128/iai.05267-11
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Yersinia pestis Infection Decreases with Age in B10.T(6R) Mice

Abstract: We demonstrate that 2-month-old female B10.T(6R) mice are highly resistant to systemic infection with the KIM5 strain of Yersinia pestis and that B10.T(6R) mice become susceptible to Y. pestis infection by the age of 5 months. In this study, young (2-month-old) and middle-aged (5-to 12-month-old) B10.T(6R) mice were infected with equal CFU counts of Y. pestis. The 50% lethal dose (LD 50 ) for young B10.T(6R) mice was ϳ1.4 ؋ 10 4 CFU, while middle-aged B10.T(6R) mice exhibited an LD 50 of ϳ60 CFU. Elevated bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…A recent study using fully virulent plague pathogens found that multiple loci were required for mice to survive in a Y. pestis subcutaneous infection model (32)(33)(34) (12), and DBA2/J mice (M. Tencati and R. Tapping, unpublished data). The resistance in BALB/cJ mice has been localized to chromosome 17, whereas at least part of the resistance in 129 mice localizes to chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study using fully virulent plague pathogens found that multiple loci were required for mice to survive in a Y. pestis subcutaneous infection model (32)(33)(34) (12), and DBA2/J mice (M. Tencati and R. Tapping, unpublished data). The resistance in BALB/cJ mice has been localized to chromosome 17, whereas at least part of the resistance in 129 mice localizes to chromosome 1.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore chose to use inbred mice as a model to identify genes that may confer resistance against plague. We and others subsequently identified several inbred strains of mice that are resistant (11)(12)(13)(14). Resistance of the 129 line was first identified by Congleton et al in a pigmentation locus-negative (pgm Ϫ ) infection model of plague (11) but not for a fully virulent Y. pestis strain.…”
mentioning
confidence: 99%
“…Shin et al reported similar data using murine infection models of Clostridum difficile, and also hypothesized that this altered susceptibility to disease could be attributed, at least to some extent, to altered innate immunity associated with microbiota-dependent changes associated with age [81,82]. There have been several reports indicating a sex bias associated with Yersinia pestis susceptibility, with female mice being more resistant to infection [83][84][85]. Additionally, Lambert and coworkers demonstrated via several parameters that older mice are also more susceptible to plague disease compared to younger mice [84].…”
Section: Discussionmentioning
confidence: 82%
“…There have been several reports indicating a sex bias associated with Yersinia pestis susceptibility, with female mice being more resistant to infection [83][84][85]. Additionally, Lambert and coworkers demonstrated via several parameters that older mice are also more susceptible to plague disease compared to younger mice [84]. Using the Francisella live vaccine strain as a surrogate pathogen, Mares et al identified no significant differences associated with age and survival; they did, however, note several important differences that were impacted in aged mice, including polymorphonuclear neutrophil infiltration kinetics and cytokine expression levels [86].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research from our laboratory has demonstrated differences in susceptibility of B10.T (6R) mice systemically infected with the KIM5 strain of Y. pestis. This difference was age dependent, where 2-month-old mice were more resistant than 5-to 12-month-old mice, with a difference in LD 50 of over 2 log (22).…”
mentioning
confidence: 98%